2015
DOI: 10.1002/2015gl065004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic reconnection in the near‐Mars magnetotail: MAVEN observations

Abstract: We report Mars Atmosphere and Volatile EvolutioN (MAVEN) observations of electrons, ions, and magnetic fields which provide comprehensive demonstration of magnetic reconnection signatures in the Martian magnetotail. In the near‐Mars tail current sheet at XMSO∼−1.3RM, trapped electrons with two‐sided loss cones were observed, indicating the closed magnetic field topology. In the closed field region, MAVEN observed Hall magnetic field signatures and Marsward bulk flows of H+, O+, and normalO2+ ions, which sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 47 publications
9
96
0
Order By: Relevance
“…The low indicates the dominant magnetic pres- sure as expected in the MPR (e.g., Ma et al, 2004). The heavier species display smaller V L changes (∼13 km/s for H + , ∼3 km/s for O + , and ∼2 km/s for O + 2 ions), suggesting that these ions are still unmagnetized and their motions are controlled mostly by electric fields, as is the case for reconnection events observed in the nightside magnetotail (Harada et al, 2015. The northward flow is opposite to southward flows nominally expected in the southern hemisphere (diverging plasma flows from the subsolar point toward the flank).…”
Section: Geophysical Research Lettersmentioning
confidence: 89%
“…The low indicates the dominant magnetic pres- sure as expected in the MPR (e.g., Ma et al, 2004). The heavier species display smaller V L changes (∼13 km/s for H + , ∼3 km/s for O + , and ∼2 km/s for O + 2 ions), suggesting that these ions are still unmagnetized and their motions are controlled mostly by electric fields, as is the case for reconnection events observed in the nightside magnetotail (Harada et al, 2015. The northward flow is opposite to southward flows nominally expected in the southern hemisphere (diverging plasma flows from the subsolar point toward the flank).…”
Section: Geophysical Research Lettersmentioning
confidence: 89%
“…At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail. At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail.…”
Section: 1029/2018gl077251mentioning
confidence: 99%
“…A diversity of plasma characteristics in the Martian CS manifests in a wide range of estimated half‐thicknesses ( L ) from L ≤ 100 km (e.g., Halekas et al, ) to a few hundreds of kilometeres (e.g. Harada et al, , ). The comparison of the CS half‐thickness with particle thermal gyroradius and inertial length allowed Harada et al () to conclude that in a thin CS, protons and/or electrons carry the electric current, while in a thick CS, the role of quasi‐adiabatic heavy ions (O + ) becomes important.…”
Section: Introductionmentioning
confidence: 99%